Social networks of patients with chronic skin lesions: nursing care - Luciana Alves Bandeira; Maxuel Cruz dos Santos; Êrica Rosalba Mallmann Duarte; Andrea Gonçalves Bandeira; Deise Lisboa Riquinho; Letícia Becker Vieira
ABSTRACT Objective: To describe the social networks of patients with chronic skin damages. Method: A qualitative study conducted through semi-structured interviews with nine subjects with chronic skin lesions from June 2016 to March 2017; we used the theoretical-methodological framework of Lia Sanicola's Social Network. Results: The analysis of the relational maps revealed that the primary network was formed mainly by relatives and neighbors; its characteristics, such as: reduced size, low density and few exchanges/relationships, configures fragility in these links. The secondary network was essentially described by health services, and the nurse was cited as a linker in the therapeutic process. Final considerations: Faced with the fragility of the links and social isolation, the primary health care professionals are fundamental foundations for the construction of networks of social support and care for patients with chronic skin lesions.